Photoinduced charge transfer: from photography to solar energy. (1st May 2017) - De Castro, Catherine; Dimitrov, Stoichko; Burrows, Hugh; Douglas, Peter; Davies, Matthew
To celebrate the centenary of Science Progress we offer a short survey of the progress made over the past one hundred years in the research and application of photoinduced charge transfer. After a brief historical overview and introduction to photoinduced charge transfer, we discuss developments in the theory and practice of photography, photovoltaics, photocatalysis, fluorescent probes and chemosensing.